Analysis of The Influence of Professionalism Attitude And Organizational Culture in Ethical Decision Making of Tax Consultants Mediated by Machiavelisnme - Rahmawati, Ana Dwi; Handoko, Yunus; Rachmawati, Ike Kusdyah (JAMPARING: Jurnal Akuntansi Manajemen Pariwisata dan Pembelajaran Konseling, 2025)
Research Aims: Tax consultants have an important role in increasing the amount of state tax revenue, this study aims to explore the important role of tax consultants in ethical decision making based on professional attitudes, organizational culture and Machiavellianism. Design/methodology/approach: Used a quantitative approach through statistical analysis of data sources originating from tax consultants who are members of the Malang Branch of IKPI, data analysis was carried out by solving Structural Equation Modelling. Research Findings: The study indicate that organizational culture and Machiavellianism have an effect on encouraging ethical decision making by tax consultants, but not for professionalism. Machiavellianism is not able to be a mediating variable in this relationship. Theoretical Contribution/Originality: This research can directly and indirectly contribute academically and practically; academically, this research serves as a foundation for further research in research on organizational behaviors such as ethical decision making of tax consultants, with the inclusion of several additional variables, such as Machiavellianism, professional attitude and organizational culture.